Anthriscus nemorosa essential oil inhalation prevents memory impairment, anxiety and depression in scopolamine-treated rats - Bağcı, Eyüp; Akbaba, Emel Aydın; Ungureanu, Eugen; Hritcu, Lucian (My University, 2016)
Anthriscus nemorosa (Bieb.) Sprengel is used for medicinal purposes in traditional medicine around the world, including Turkey. Ethnobotanical studies suggest that Anthriscus essential oil could improve memory in Alzheimer’s disease. The current study was hypothesized to investigate the beneficial effects of inhaled Anthriscus nemorosa essential oil on memory, anxiety and depression in scopolamine-treated rats. Anthriscus nemorosa essential oil was administered by inhalation in the doses of 1% and 3% for 21 continuous days and scopolamine (0.7 mg/kg) was injected intraperitoneally 30 min before the behavioral testing. Y-maze and radial arm-maze tests were used for assessing memory processes. Also, the anxiety and depressive responses were studied by elevated plus-maze and forced swimming tests. As expected, the scopolamine alone-treated rats exhibited the following: decrease the percentage of the spontaneous alternation in Y-maze test, increase the number of working and reference memory errors in radial arm-maze test, decrease of the exploratory activity, the percentage of the time spent and the number of entries in the open arm within elevated plus-maze test and decrease of swimming time and increase of immobility time within forced swimming test. However, dual scopolamine and Anthriscus nemorosa essential oil-treated rats showed significant improvement of memory formation and exhibited anxiolytic- and antidepressant-like effects in scopolamine-treated rats. These results suggest that Anthriscus nemorosa essential oil inhalation can prevent scopolamineinduced memory impairment, anxiety and depression.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Scopolamine; Memory; Anxiety; depression; Anthriscus nemorosa essential oil; Alzheimer’s disease